The DLSU Board of Trustees' second quarterly meeting - Jayme, Vicente (Animo Repository, 1981)
The DLSU Board of Trustees held its second quarterly meeting on September 14, 1981. Highlight of the meeting was the presentation of a plaque of appreciation to outgoing chairman Vicente Jayme. Jayme has been chairman of the Board since 1978, and Board member since 1974.